Offshore Crude Oil Disrupts Retinoid Signaling and Eye Development in Larval Atlantic Haddock - Lie, Kai K.; Meier, Sonnich; Sørhus, Elin; Edvardsen, Rolf B.; Karlsen, Ørjan; Olsvik, Pål A. (Frontiers in Marine Science, 2019)
The aim of this study was to examine the impact of dispersed crude oil on retinoid metabolism and signaling in developing haddock larvae (Melanogrammus aeglefinus). Retinoids and its active metabolites are involved in the regulation of several developmental processes as cell differentiation, growth and limb patterning. Thus, disruption of retinoid signaling, especially during early developmental stages, may have detrimental effects on the organism. In the present study, crude oil exposure during embryonic development and early larvae development disrupted vitamin A signaling by affecting retinoid levels and genes involved in retinoid metabolism. The disruption of retinoid signaling was also evident when looking at the gene expression pattern at several time-points during and after exposure, demonstrating the complexity and temporal factor of retinoid signaling disruption. Exposure during the embryonic period (pre hatch) resulted in reduced eye size and increased incidence of abnormal eye morphology. The observed changes in expression of retinoid metabolic genes related to the visual cycle indicates that there is a link between the modulated retinoid levels (all-trans retinoic acid and retinol) and increased incidence of abnormal eye development as a result of crude oil exposure. This is the first study to demonstrate disrupted retinoid signaling in fish following crude oil exposure at environmental relevant levels, giving novel insight in to the mechanism of toxicity.